2002
DOI: 10.1128/cdli.9.6.1324-1327.2002
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Cytokines and Soluble Cellular Receptors in the Sera of Children with Acute Chagas' Disease

Abstract: Cytokines and soluble cellular receptors are involved in inflammatory processes and probably in the pathogenesis of parasite and bacterial diseases. In a previous study, we reported increased levels of soluble receptors of interleukin-2 (sIL2-R) in children with acute Chagas' disease, one of the main parasitic infections that is endemic in Latin America. We sought to analyze the pattern of different cytokines and soluble receptors in the sera of children with chagasic infection. Children with acute and indeter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…It has been suggested that chronic TNF-α production prior to heart failure may play a role in chronic Chagas disease cardiomyopathy progression (Ferreira et al 2003). A similar level of cytokine production in sera of acute chagasic children, compared to NI, has been described previously (Moretti et al 2002). Although the present results showed no differences between IL-10 and IFN-γ levels in CARD and IND patients, the IND patients displayed a positive correlation between inflammatory and regulatory cytokine production, indicating a controlled immune response.…”
Section: Discussionmentioning
confidence: 50%
“…It has been suggested that chronic TNF-α production prior to heart failure may play a role in chronic Chagas disease cardiomyopathy progression (Ferreira et al 2003). A similar level of cytokine production in sera of acute chagasic children, compared to NI, has been described previously (Moretti et al 2002). Although the present results showed no differences between IL-10 and IFN-γ levels in CARD and IND patients, the IND patients displayed a positive correlation between inflammatory and regulatory cytokine production, indicating a controlled immune response.…”
Section: Discussionmentioning
confidence: 50%
“…Taken together, these results show that vaccination with T. rangeli made it possible to induce a profile of the cytokines different from that of the non immunized-infected mice, with a delicate balance between TH1 and TH2, suitable for overcome the infection. This modulation of the synthesis and liberation of cytokines and soluble receptors was also observed during the acute period of natural human infection [41] . On the other hand, during the process of invading the host cell, T. cruzi interacts with different receptors of the macrophage to induce its own phagocytosis.…”
Section: Soluble Mediators and Cellsmentioning
confidence: 63%
“…On the other hand, the changes that lead to (Dias et al 2002), there are some factors, such as the disease's enzootic nature, as well as human migrations and deforestation (Coura et al 2002), that contribute to the continuous presence of the disease, which is more frequent in children up to 14 years old. Studies to confirm the presence of the parasite in this population are more effective to determine the presence of active transmission than studies in older individuals (Añez et al 1999;Moretti et al 2002). The remarkable similarity between murine and human immune systems (Dos Reis and Lopes 2000) allows the demonstration that, with respect to the inherent parameters of the T. cruzi-mammal relationship, animal age is one of the most important parameters regarding the development of this parasitosis.…”
Section: Discussionmentioning
confidence: 99%